Modelo pedagógico para la enseñanza de las normas internacionales de auditoría y aseguramiento de la información en un ambiente virtual de aprendizaje (2018)
The convergence to the International Financial Reporting Standards - IFRS - in Colombia brought important challenges for the accounting profession, mainly concerning the paradigm shift of the users of the information and their need to obtain reliable and relevant financial information for their Investment and Financing decision-making. In effect, the objective of this research was to design a pedagogical model applied to the teaching of International Standards on Auditing and Information Assurance, which would respond to the needs of future accountants to be able to provide assurance that the financial statements are under IFRS. In this regard, it was started by identifying the competences that future financial auditors should develop, to determine the contents to be taught, which were complemented by the incorporation of active teaching-learning methodologies that obey the new pedagogical models with a competency-based approach. The result of this research is summarized in a pedagogical model applied in the design and structuring of the course “Financial Assurance”, proposing the use of the case method and collaborative learning as applicable strategies in virtual learning environments.